Pluralist perspectives and diverse responses: Exploring multiplexed framing in incumbent responses to digital disruption - Fraser, J; Ansari, SS (Elsevier, 2020)
Research applying a socio-cognitive lens to disruptive digital innovation often fails to account for intra-firm heterogeneity in how an established incumbent frames and responds to disruptive innovation. To explore the heterogeneous framing processes involved within a firm, we conducted an in-depth case study of the response of a multinational insurance group to a digitally-led disruptive innovation: the rise of internet-based general insurance aggregator platforms between 2002 and 2007. We map different response frames across three separate framing dimensions: the Challenge Type, Response Urgency and Firm Heritage, and explore their interplay in shaping responses to disruption. We introduce the idea of multiplexed framing – comprised of multiple, non-binary frames – and propose that these are holographically distributed – such that conflicting frames can be held by members of the same organizational department or group. This allows managers to leverage the ambiguity generated by multiplexed frames to select the same response strategies for different reasons leading to an equifinal resolution of conflict. We show how such framing enables the organization to trial and adaptively iterate between different strategic responses to disruptive innovation, particularly amid high uncertainty and ambiguity.